2022
DOI: 10.1172/jci.insight.162085
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of insulin resistance with change in bone mineral density in midlife women

Abstract: Although there is wide recognition that type 2 diabetes mellitus (DM2) is a risk factor for fractures (1), the effects of insulin resistance (a key pathophysiologic mechanism in DM2) on bone remain uncertain. In vitro, insulin signaling promotes osteoblast differentiation, proliferation, and function (2-4). However, in the in vivo models of insulin resistance, insulin signaling leads to expansion of bone marrow adipose tissue, decreased trabecular bone mineral density (BMD), and decreased cortical thickness (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…In a cross-sectional examination of participants in the Korean National Health and Nutrition Examination Study, greater serum insulin was associated with higher BMD when insulin resistance (estimated using HOMA-IR) was in the lowest quartile; in contrast, at higher HOMA-IR levels, greater serum insulin correlated with lower BMD [19]. We reported similar findings in a longitudinal analysis of insulin resistance and BMD in the Study of Women's Health Across the Nation (SWAN) [20 ▪ ]. At lower levels, greater HOMA-IR over time was associated with slower bone loss.…”
Section: Prediabetes and Bonesupporting
confidence: 53%
“…In a cross-sectional examination of participants in the Korean National Health and Nutrition Examination Study, greater serum insulin was associated with higher BMD when insulin resistance (estimated using HOMA-IR) was in the lowest quartile; in contrast, at higher HOMA-IR levels, greater serum insulin correlated with lower BMD [19]. We reported similar findings in a longitudinal analysis of insulin resistance and BMD in the Study of Women's Health Across the Nation (SWAN) [20 ▪ ]. At lower levels, greater HOMA-IR over time was associated with slower bone loss.…”
Section: Prediabetes and Bonesupporting
confidence: 53%
“…Several recent SWAN analyses showed that prediabetes was associated with worse trabecular bone microarchitecture 8 and that greater insulin resistance was associated with diminished bone strength 10 and faster BMD loss. 22 In other cohorts, prediabetes was associated with lower bone turnover, 6,7 which can contribute to an accumulation of advanced glycation end products in bone and suboptimal bone material properties. [28][29][30][31] Establishing whether prediabetes is a risk factor for fractures has potential public health implications.…”
Section: Discussionmentioning
confidence: 97%
“…Our results add to a body of data suggesting that prediabetes is detrimental to bone health. Several recent SWAN analyses showed that prediabetes was associated with worse trabecular bone microarchitecture and that greater insulin resistance was associated with diminished bone strength and faster BMD loss . In other cohorts, prediabetes was associated with lower bone turnover, which can contribute to an accumulation of advanced glycation end products in bone and suboptimal bone material properties …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these metabolic changes can have an influence on the bone structure in PLWHIV is an issue that remains to be elucidated. However, diabetes, insulin resistance and NAFLD have all been reported to be associated with an increased risk of osteoporosis and fracture in individuals without HIV [ 64 , 65 , 66 , 67 ]. Xu et al studied the association between NAFLD and BMD in 89 HIV-infected patients receiving long-term TDF-based ARV for more than three years.…”
Section: Hiv and Endocrine/metabolic Changes Relating To Impact On Bonesmentioning
confidence: 99%